1994
DOI: 10.1002/pen.760340602
|View full text |Cite
|
Sign up to set email alerts
|

Quiescent polymer crystallization: Modelling and measurements

Abstract: The problem of predicting nonisothermal crystallization kinetics based on isothermal data is considered, with reference to the difficulties involved, both experimental and theoretical. The kinetic model used is the differential form of the Nakamura equation which is an extension of the Avrami equation so as to apply to nonisothermal crystallization. Nonisothermal induction times are obtained from isothermal induction times according to the concept of induction time index. The theory of Hoffman Lauritzen is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0
5

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(131 citation statements)
references
References 18 publications
3
123
0
5
Order By: Relevance
“…The crystallization rates at different temperatures were expressed in the form of reciprocal of crystallization half-time t 1/2 . Using Hoffman-Lauritzen relationship between the radial growth rate of crystal and crystallization temperature based on crystallization regime theory [25], and following Chan and Isayev [26] (1/t 1/2 ) and (1/t 1/2 ) 0 were used to Figure 4. The determination of the equilibrium melting temperature substitute for the growth rate G and a pre-exponential factor G 0 , respectively.…”
Section: The Fold Surface Free Energy Based On Hoffman-lauritzen Relamentioning
confidence: 99%
“…The crystallization rates at different temperatures were expressed in the form of reciprocal of crystallization half-time t 1/2 . Using Hoffman-Lauritzen relationship between the radial growth rate of crystal and crystallization temperature based on crystallization regime theory [25], and following Chan and Isayev [26] (1/t 1/2 ) and (1/t 1/2 ) 0 were used to Figure 4. The determination of the equilibrium melting temperature substitute for the growth rate G and a pre-exponential factor G 0 , respectively.…”
Section: The Fold Surface Free Energy Based On Hoffman-lauritzen Relamentioning
confidence: 99%
“…The melted samples were then cooled at various constant cooling rates of 0.5, 2.5, 5 ,10, 20, 50, 75°C/min. Before the samples were tested, a standard indium calibration was run by heating at a rate of 20°C/min in order to correct all the results of temperature lag between the sample and the DSC furnace 10 at high cooling rate runs, as discussed in Appendix A.…”
Section: Methodsmentioning
confidence: 99%
“…It is observed that 0(Tin) is only dependent on n, i.e., independent of heating and cooling rates q, as it is expected following the theory presented in the previous sections. Moreover, every experimental, nonisothermal crystallization curve 0(T) shows only one inflexion point independent of the cooling or heating rate q, 9 facilitating the application of the theory based on apparent m-order reaction functions of the type given by eq 1. The highest precision in determining the A vrami index n graphically is achieved for small slopes 80(T)/8Tlr=T,n• i.e., a low Tin for melt crystallization and a high Tin for cold-crystallization.…”
Section: Aka(t) =K (T)(__!i_)mentioning
confidence: 99%
“…Small slopes are technically accomplished by performing DSC-measurements with relatively high cooling or heating rates q. 9 Then-values, which have been evaluated graphically with the inflexion-point method, are equal for cold-and melt-crystallization (n 2.4). 6 • 9 The isokinetic approach of Nakamura et al 4 is experimentally clearly supported by the results displayed in Tables I and II, since a approximately symmetrical distribution of k(Tin) is obtained for cold-resp.…”
Section: Aka(t) =K (T)(__!i_)mentioning
confidence: 99%